The benefits of Square dancing as a means of physical activity for Czech dancers with hearing loss - Petra Kurková; Jessica Jayne Maertin (Palacký University Olomouc, 2014)
Background: Hearing, a strong line of communication that enables individuals to learn about the world around them, is a major factor contributing to the psychomotor development of every individual. Hearing loss can also affect the conception and perception of sounds and rhythm. Objective: The purpose of this study was to describe and analyse the benefits of Square and Round dancing for persons with hearing loss. Methods: The present study is an analytic-descriptive qualitative research. The sample was constituted non-probabilistically based on the following features: a) a participant had to have hearing problems (hearing loss) and b) had to have participated regularly in Square dance for at least two years. Each participant was asked to name possible people to be interviewed (snowball technique). We analysed the data of 7 individuals (6 males and 1 female) with hearing loss. The mean age of the dancers with hearing loss was 51.3 years. The participants had no cochlear implants or any other physical or vision related impairments. Results: The present findings constitute the first published survey regarding Czech Square dancers' status, their family's hearing status, hearing aid use, communication preference, education in integrated or segregated settings, the influence of family background on dance initiation, coach preference (hearing or deaf), and the environment for participation in Square dance as a mode of physical activity with regular dancers and with dancers with hearing loss as well. In the present sample of dancers with hearing loss, most were from hearing families and had hearing siblings. The degree to which individuals with hearing loss feel comfortable with the hearing world appears to influence their later preference for participating in regular, as opposed to segregated, physical activities. More than half of the dancers with hearing loss who participated in this research study would like to meet with the deaf minority. One of the main reasons for this is to get to know new people and to share experiences with those who have the same problems with hearing. Conclusion: The present study emphasizes the need for the additional support and promotion of the accessibility to their chosen physical activities for individuals with hearing loss. This will be best accomplished if both the deaf and hearing communities work together.